Juvenile systemic lupus erythematosus presenting as pancarditis - D. O'Leary; C. O'Connor; L. Nertney; E. J. MacDermott; D. Mullane; O. Franklin; O. G. Killeen (BMC, 2019)
Abstract Background Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with marked variation in its clinical presentation. Juvenile SLE (jSLE) accounts for 15-20% of all cases and is diagnosed when SLE manifests before 18 years of age. Pancarditis is a rare complication of SLE, regardless of age of disease onset. Case presentation We report a case of jSLE in a 15 year old Caucasian female presenting with an acute episode of pancarditis and multiorgan dysfunction who was successfully treated with systemic corticosteroids and cyclophosphamide. Conclusion Pancarditis can be a presenting feature of jSLE which was previously unreported. A high index of suspicion for severe cardiac involvement is required at all stages of disease.